Exercises for the improvement of the filtered passes in the soccer team of Guantanamo - Omar Vázquez-Pozo; Hirbins Manuel Dopico-Pérez (Universidad de Guantánamo, 2019)
An experimental study was developed to expose the results of the offensive technical-tactical exercises for the improvement of the leaked passes of the Guantanamo soccer team. It is based on the different theories that revolve around this theme and the main research references of the subject. In the different concepts of tactics issued by the different authors of sports literature, as well as in the diagnosis of the current situation presented by these athletes. The study aims to offer exercises that will contribute to the improvement of this technical element in the team studied.